2015
DOI: 10.1074/jbc.m115.669309
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Lzap Suppresses Wnt/β-Catenin Signaling to Promote Zebrafish Embryonic Ventral Cell Fates via the Suppression of Inhibitory Phosphorylation of Glycogen Synthase Kinase 3

Abstract: Background: Lzap is a novel tumor suppressor. Results: Elimination of Lzap in fish embryos or in a human tongue carcinoma cell line increases inhibitory phosphorylation of GSK3, which controls much cellular signaling, including Wnt/␤-catenin signaling. Conclusion: Lzap promotes GSK3 activity. Significance: This introduces a new regulator of GSK3 and a potential target for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 63 publications
(84 reference statements)
0
18
0
Order By: Relevance
“…In HNSCCs, CDK5RAP3 was shown to suppress NF-κB by reducing the phosphorylation of RelA [ 12 ]. Lin KY et al found that CDK5RAP3 also suppressed Wnt/β-catenin signaling via the suppression of GSK-3β phosphorylation in zebrafish embryos [ 17 ]. However, how CDK5RAP3 suppresses GSK-3β phosphorylation is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCCs, CDK5RAP3 was shown to suppress NF-κB by reducing the phosphorylation of RelA [ 12 ]. Lin KY et al found that CDK5RAP3 also suppressed Wnt/β-catenin signaling via the suppression of GSK-3β phosphorylation in zebrafish embryos [ 17 ]. However, how CDK5RAP3 suppresses GSK-3β phosphorylation is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Twa1a morphants showed reduced expression of the dorsal markers chordin , goosecoid and otx2 , and expanded expression of the ventral markers eve1 and gata2 ( Figure 7C and 7D ) 38 . To test if these defects were caused by Wnt signaling deficiency, we examined the expression of the maternal Wnt target gene bozozok ( boz ) 39 , 40 , and found that depletion of Twa1a markedly decreased boz expression ( Figure 7E and 7F ). Importantly, all of these ventralized phenotypes were efficiently reversed by morpholino-resistant Twa1 mRNA, but not by morpholino-resistant Twa1 -Δ CRA mRNA ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type zebrafish (strain AB) were maintained at 28.5 °C using standard protocols. Procedures for animal staging and injection were performed as described 37 , 38 , 39 , 40 . Synthetic RNAs were transcribed in vitro using pCS2-Twa1a, Twa1b or Twa1a-ΔCRA vectors with MessageMachine (Ambion).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations